The study of behavior in the analytical-behavioral context: a critical historicity and ethical-political reflections - Barreto, Wanderson; Toassa, Gisele (Perspectivas em Análise do Comportamento, 2022)
This essay critically discusses the historical aspects of the study of human behavior in Psychology, as well as the ethical-political implications related to this theme. A historical outline of the construction of the category “behavior” for Psychology throughout the 20th century is carried out, problematizing the possible ethical-political impacts of behavioral science practices. It is a work structured in three sections: 1) Behavior: A category under the north-American scientific domain, in which it is discussed how the study of behavior was built from the predominance of traditional sciences and the ideal of scientific objectivity; 2) The reconstruction of “behavior” in Psychology from Skinner’s thought, in which the strengthening of the idea of behavior as a theme of Psychology from the Radical Behaviorist perspective is pointed out; and 3) Is a Behavioral Science with ethical-political responsibilities possible?, which seeks to question the association between “behavior” and “control” in a behavioral science and the resulting ethical-political implications. We conclude that: 1) “Behavior” as an object of investigation contributed so that Psychology could approach the natural sciences; 2) Skinner’s Radical Behaviorism has strengthened the idea that the study of behavior can contribute to the reach and solution of social problems; and 3) It is possible that behavioral scientists do enterprises responsible from critical studies on the uses of science to equip and strengthen dominant groups and the possibilities of using scientific knowledge to face certain mechanisms of domination.